1992
DOI: 10.1126/science.1615323
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Solvent Viscosity in the Dynamics of Protein Conformational Changes

Abstract: Nanosecond lasers were used to measure the rate of conformational changes in myoglobin after ligand dissociation at ambient temperatures. At low solvent viscosities the rate is independent of viscosity, but at high viscosities it depends on approximately the inverse first power of the viscosity. Kramers theory for unimolecular rate processes can be used to explain this result if the friction term is modified to include protein as well as solvent friction. The theory and experiment suggest that the dominant fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

37
647
4

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 555 publications
(688 citation statements)
references
References 30 publications
37
647
4
Order By: Relevance
“…The frictional coupling between protein motions and water dynamics has been suggested that fluctuations of the hydration water can slave the protein dynamics and thus affect its function (29,56,57). (where proportionality between the hydration level and the area of charged and polar surfaces was assumed), but is close to the value published for small solute molecules.…”
Section: Discussionsupporting
confidence: 52%
“…The frictional coupling between protein motions and water dynamics has been suggested that fluctuations of the hydration water can slave the protein dynamics and thus affect its function (29,56,57). (where proportionality between the hydration level and the area of charged and polar surfaces was assumed), but is close to the value published for small solute molecules.…”
Section: Discussionsupporting
confidence: 52%
“…[1][2][3]13 This band exhibits timedependent spectral shifts after MbCO photolysis, and this has been taken to be an indicator of protein conformational changes in response to bond breaking and recombination. [4][5][6]13,14 The absorption and Stark spectra of deoxyMb are presented in Figure 1, 15 and the values of parameters extracted from an analysis of the Stark spectra are summarized in Table 1. The Stark spectrum shows clear features for bands I and III, as well as for the Q and B bands; the broad negative base line offset below about 16 000 cm -1 may be associated with the Stark effect on band II.…”
mentioning
confidence: 99%
“…Ligand and substituent effects have been systematically assigned, and the focus in recent years has shifted toward static and dynamic band shifts that characterize biological function. [1][2][3][4][5][6] The origins of these band shifts can be roughly divided into specific chemical effects, e.g., changes in ligand or heme substituents, and more global environmental shifts, typically originating in changes in the electrostatic field around the chromophore. The latter effects are Stark shifts due to the interaction between the change in dipole moment (∆µ) and polarizability (∆R) of the chromophore with the electrostatic field of the ordered environment.…”
mentioning
confidence: 99%
“…The roughness ε is about 1 to 4 B kT in all cases studied. In case of proteins, it is suggested that intrachain collisions is the main source of roughness in energy landscape [65,70,147]. In my experiments, intrachain collisions might occur but are rare since the molecule is unfolded and there is no compact region.…”
Section: Discussionmentioning
confidence: 99%
“…Recently it was shown that internal friction varies substantially along the folding pathway of a peptide chain which suggests a connection between friction and formation of hydrogen bonds upon folding [66]. While such studies on proteins are ubiquitous [68][69][70], there is obviously a lack of experimental data on roughness of DNA and RNA conformational transition. …”
Section: Internal Frictionmentioning
confidence: 99%